Butyl hydroxytoluene (BHT)-induced oxidative stress: Effects on serum lipids and cardiac energy metabolism in rats - Faine, L. A.; Rodrigues, H. G.; Galhardi, C. M.; Ebaid, GMX; Diniz, Y. S.; Fernandes, AAH; Novelli, ELB (Elsevier B.V., 2006)
Recent lines of evidences indicate that several pathological conditions, as cardiovascular diseases, are associated with oxidative stress. In order to validate a butylated hydroxytoluene (BHT)-induced experimental model of oxidative stress in the cardiac tissue and serum lipids, 12 Wistar rats were divided into two groups, a control group and the BHT group, Which received BHT i.p. twice a week (1500 mg/kg body Weight) during 30 days. BHT group presented lower body weight gain and heart weight. BHT induced toxic effects on serum through increased triacylglycerols (TG), VLDL and LDL-cholesterol concentrations. The heart of BHT animals showed alteration of antioxidant defenses and increased concentrations of lipid hydroperoxides, indicating elevated lipoperoxidation. TG concentrations and lactate dehydrogenase activities were elevated in the cardiac Muscle of BHT animals. Thus, long-term administration of BHT is capable to induce oxidative and metabolic alterations similarly to some pathological disorders, constituting an efficient experimental model to health scientific research. (c) 2005 Elsevier GrnbH. All rights reserved.
Keywords: butylatcd hydroxytoluene; oxidative stress; heart; energy metabolism; serum lipids; cholesterol; triacylglycerols; lipid peroxidation; antioxidant enzymes